2018
DOI: 10.1038/s41391-018-0059-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of androgen deprivation therapy with thromboembolic events in patients with prostate cancer: a systematic review and meta-analysis

Abstract: GnRH agonists alone, GnRH plus AA, and AA alone cause excess DVT in men with PCa after controlling the demographic and disease characteristics and other confounding factors, although statistically significant difference was not observed in orchiectomy group. Additionally, GnRH agonists alone and orchiectomy can increase the incidence of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Our data confirmed this tenet, because most men died of causes other than prostate cancer, and long-term ADT ≥2 years worsened not only OCM but also OS. Several adverse effects of ADT have been reported: 5 weight gain, decreased muscle mass and increased insulin resistance, decreased bone mineral density, decreased libido and sexual dysfunction, hot flashes, gynecomastia, reduced testicle size, anemia, fatigue, diabetes, cardiovascular events (myocardial infarction [MI] and sudden cardiac death) [ 14 , 15 ], cerebrovascular diseases [ 15 ], kidney injury [ 16 ], dementia [ 17 ], and thromboembolic events [ 18 , 19 ]. Abdollah et al, in their study including 137,524 patients with non-metastatic prostate cancer treated between 1995 and 2009, reported that treatment with medical ADT may increase the risk of OCM [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirmed this tenet, because most men died of causes other than prostate cancer, and long-term ADT ≥2 years worsened not only OCM but also OS. Several adverse effects of ADT have been reported: 5 weight gain, decreased muscle mass and increased insulin resistance, decreased bone mineral density, decreased libido and sexual dysfunction, hot flashes, gynecomastia, reduced testicle size, anemia, fatigue, diabetes, cardiovascular events (myocardial infarction [MI] and sudden cardiac death) [ 14 , 15 ], cerebrovascular diseases [ 15 ], kidney injury [ 16 ], dementia [ 17 ], and thromboembolic events [ 18 , 19 ]. Abdollah et al, in their study including 137,524 patients with non-metastatic prostate cancer treated between 1995 and 2009, reported that treatment with medical ADT may increase the risk of OCM [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many meta-analyses have shown the effects of ADT on cognitive function, cardiovascular complications, and thromboembolic events in PCa patients [41,42,43,44,45]; however, to the best of our knowledge, our study is the first to show the effect of ADT on bone health in patients with PCa. Furthermore, we have identified a significant relationship between ADT and BMD reduction.…”
Section: Discussionmentioning
confidence: 63%
“…There was also a significant association between ADT and hypertension, particularly for second generation therapies, abiraterone and enzalutamide. Other vascular disorders like thromboembolic events also showed a significant association with GnRHa alone, CAB, anti-androgen alone, oestrogen and orchiectomy (10,18). For vasomotor flashing, enzalutamide had a significant increased risk and anti-androgens a significantly lower risk than other types of ADT (14,15,25,29,57).…”
Section: Discussionmentioning
confidence: 91%
“…Population-based studies of men receiving ADT for PC have revealed an association between ADT and increased risk of thromboembolic events such as deep vein thrombosis (DVT) and pulmonary embolus (PE). Two meta-analyses examined the evidence for ADT associated thromboembolic events (10,18).…”
Section: B Thromboembolic Eventsmentioning
confidence: 99%
See 1 more Smart Citation